2012
DOI: 10.1016/j.physletb.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of polarized bZ production at LHC

Abstract: We consider the Z polarization asymmetry A_Z=(σ(ZR)−σ(ZL))/(σ(ZR)+σ(ZL)) in the process of associated bZ production at the LHC. We show that in the Standard Model (SM) this quantity is essentially given by its Born approximation, remaining almost unaffected by QCD scales and parton distribution functions variations as well as by electroweak corrections. The theoretical quantity that appears in A_Z is the same that provides the LEP1 Z→bb¯ forward–backward asymmetry, the only measured observable still in some co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Therefore, the Z+b cross section measurement can be exploited for studying the b-quark distribution function. The b-PDF plays a relevant role in t-channel single top production [44], Beyond Standard Model (BSM) phenomenology [45,46] and electroweak physics [47,48]. The production of heavy flavours in association with a Z gauge boson is subject to sizable uncertainty on both the experimental and theoretical sides.…”
Section: Gauge Boson Productionmentioning
confidence: 99%
“…Therefore, the Z+b cross section measurement can be exploited for studying the b-quark distribution function. The b-PDF plays a relevant role in t-channel single top production [44], Beyond Standard Model (BSM) phenomenology [45,46] and electroweak physics [47,48]. The production of heavy flavours in association with a Z gauge boson is subject to sizable uncertainty on both the experimental and theoretical sides.…”
Section: Gauge Boson Productionmentioning
confidence: 99%
“…Higgs fields, H = (H L , H R ) and Ĥ = ( ĤL , ĤR ), are introduced and each transforms as (4,1) and (1,4) respectively under the global symmetry. The U (4) 1 [U (4) 2 ] group is spontaneously broken down to its subgroup The original gauge symmetry SU (2) L × SU (2) R × U (1) B−L is broken down to U (1) em and generates four charged and two neutral gauge bosons: W ± , W ± , Z, and Z .…”
Section: The Left-right Twin Higgs (Lrth) Modelmentioning
confidence: 99%
“…In general, the asymmetry is a ratio of observables of similar nature. Compared to the production cross section, decay width etc, the asymmetry is almost free from theoretical uncertainties related to QCD scale and parton distribution function (PDF) set variations, which has been shown by [3,4] for the partonic processes gb → tS − and gb → Zb at the LHC, respectively. The asymmetry can be utilized to study the detailed properties of the particles and to further investigate underlying dynamics in or beyond the SM.…”
Section: Introductionmentioning
confidence: 99%
“…where σ(Z R b) and σ(Z L b) are the hadronic cross sections of Z R b and Z L b production at the LHC, respectively. Ref [8]. has shown that A Z is connected to the Zbb F B asymmetryA b F B and given its SM prediction value.…”
mentioning
confidence: 93%
“…Recently, Ref. [8] has defined the Z polarization asymmetry A Z in the subprocess gb → Zb at the LHC and has shown that A Z is strictly connected to the F B asymmetry A b F B and is almost free from the theoretical uncertainties related to QCD scale and parton distribution function (P DF ) set variations.…”
Section: Introductionmentioning
confidence: 99%